Christ & Gantenbein projects - Christ, Emanuel 1970-; Gantenbein, Christoph 1971- (Verlag der Buchhandlung Walther und Franz König, 2024)
"Projects I-III" adopts a predominantly visual format, featuring 1,800 images including photographs and sketches, 700 plans, and 45 accompanying texts. The content has been meticulously curated by Emanuel Christ and Christoph Gantenbein, who personally selected the most meaningful documents from the firm’s extensive 25-year archive. The layout, designed by Ronnie Fueglister, takes the form of a contact sheet, presenting each project in reverse chronological order — from the completed building to the initial sketches. The first featured project is a garden porch, the last of the series is the social housing Vaugirard, recently completed in Paris.
Keywords: Christ & Gantenbein; Architektur